A Discourse Analysis of American Folktale â€œthe Monkeyâ€™s Pawâ€ - Andi Tenrisanna Syam (Universitas Ahmad Dahlan, 2017)
Discourse analysis studies language in use taking into account important elements such as coherence (unity of the text) and cohesion (tools that tie together sentences, e.g. pronouns). American folktale â€œthe monkeyâ€™s pawâ€ is written by W.W. Jacobs.